2010
DOI: 10.1590/s0103-97332010000400018
|View full text |Cite
|
Sign up to set email alerts
|

Optical and electrical diagnostics of microdischarges at moderate to high pressure in argon

Abstract: Microdischarges at moderate to high pressure in argon were investigated. A hole opening diameter of 500 µm direct current (dc) microhollow cathode discharges (MHCD) were characterized by electrical measurements and optical emission spectroscopy (OES) for pressures ranging between 90 and 800 Torr and current from 5 to 20 mA. Current-voltage characteristic curves were obtained as a function of the pressure for this hole diameter. MHCD enables stable dc discharges for molybdenum electrodes material at constant Ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
2
1
0
Order By: Relevance
“…8(b). The same trend reported by using micro-discharge at medium to high pressure in argon [34]. On the other hand, a decrease in excitation temperature with an increased pressure has been reported at low-pressure argon plasma discharge [25], low power microwave plasma [31], and high pressure of in-liquid plasma in water [30].…”
Section: Considering That N(t)/u(t) Is a Standard Constant For All LIsupporting
confidence: 76%
“…8(b). The same trend reported by using micro-discharge at medium to high pressure in argon [34]. On the other hand, a decrease in excitation temperature with an increased pressure has been reported at low-pressure argon plasma discharge [25], low power microwave plasma [31], and high pressure of in-liquid plasma in water [30].…”
Section: Considering That N(t)/u(t) Is a Standard Constant For All LIsupporting
confidence: 76%
“…The apparatus used to record the optical emission spectrum from the microplasma is illustrated in figure 2; this is similar to others reported [26,[29][30][31]. A pair of achromatic lenses image the microplasma emission into a multi-mode fibre.…”
Section: Methodssupporting
confidence: 54%
“…It was found that the emission intensity of Argon lines was from 400 to 820nm correlates with the 5p-4s and 4p-4s transition. This condition indicated a high electron temperature in the observed region [31]. It may be more efficient to identify plasmas at both low-and high-pressure plasmas.…”
Section: Experimental Procedures Figure 1 High-frequency Argon Jet Pl...mentioning
confidence: 75%